The duality of civilisational rift: ecological impasse and anthropological alienation in the age of bifurcation - Vodopianov, Pavel A.; Sidorenko, Irina N. (Journal of the Belarusian State University. Sociology, 2026)
The article explores the profound interconnection between two key crises of our time: the ecological crisis and the anthropological crisis (the crisis of the human condition). This interconnection is revealed through a synthesis of the concept of global evolution and philosophical critique. It is argued that these crises are not autonomous but represent two sides of a single civilisational rift rooted in the dominance of instrumental rationality and an anthropocentric model of domination. The ecological crisis is interpreted as an external manifestation of the forgetfulness of the ontological foundations of the world, while the anthropological crisis is viewed as its internal consequence, expressed in a state of existential homelessness and ontological nihilism. As a philosophical response, the authors substantiate an evolutionary-humanistic strategy that proposes a path toward the simultaneous overcoming of two crises through the adoption of a biospheric imperative and the formation of existentially grounded responsibility.
Keywords: ecological crisis; anthropological crisis; global evolution; instrumental rationality; ontological nihilism; evolutionary-humanistic strategy; biospheric imperative; existential homelessness